Evaluasi Program Aplikasi Tulungagung Tourism Dalam Mendukung Pemulihan Pariwisata Pasca Pandemi Di Kabupaten Tulungagung - Denny, Vicky Kusuma; Sholichah, Nihayatus; Haryati, Eny (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2024)
Implementation of the Tulungagung Tourism Application Program Tulungagung Tourism in tourism development is very much needed. Currently, traveling has become a necessity for many people and it is time to optimize the tourism industry with a touch of technology and increase the commercialization of tourist areas through more modern tourism alternatives. The implementation of the Tulungagung Tourism Application Program which can be accessed via gadgets and the internet can be used as a tool for local governments to improve the quality of public services and improve the regional economy through the tourism sector. The method used in this research uses in-depth analysis techniques, namely examining problems on a case by case basis. In this research, the focus of the research study is identifying the role of the Tulungagung Tourism application in helping restore tourism in Tulungagung Regency after the pandemic. Then we will also examine what factors influence the implementation of the Tulungagung Tourism application at tourist attractions in Tulungagung Regency. The Tulungagung Regency Government has made a breakthrough in the tourism sector by providing community services in the form of an application called Tulungagung Tourism. The Tulungagung Tourism application is designed as a means or information medium prepared by the Tulungagung Regency government to make it easier for tourists to choose the best spots. The existence of the Tulungagung Tourism application is very important because it helps tourists to explore tourist destinations by using this application. In this application there are many features that make it easier for tourists to choose their tourist destination. With the Tulungagung Tourism application, Tulungagung district has become one of the areas that is most serious about developing its tourism sector massively and continues to grow. This application is one of the long-term plans for the government because there are so many tourist attractions in Tulungagung that the government automatically provides media facilities to accommodate tourists' needs.